How can environmental regulations spur international trade? The case of the EU Performance of Buildings Directive and Lessons for Asia - Matthias Helble; Adam Majoe (Asian Development Bank Institute (ADBI), 2017)
International trade is one of the key mechanisms for the diffusion of energy efficient technologies. Yet, little is known how regulations to fight climate change affect the international trade in goods needed to increase energy efficiency. This paper studies the case of the Energy Performance of Buildings Directive (EPBD), which was adopted in 2010 by the European Union (EU). The directive puts forward binding technical regulations, such as minimum efficiency requirements and energy performance certificates for buildings, and is, thus, a non-market instrument. The EPBD was supposed to be transposed into national law by the EU member states by 2012. However, the EU member states were not equally successful in fully implementing the EPBD. These implementation gaps were uncovered and quantified in a study by Ecofys (2015). Building this information into a gravity model, we test empirically whether and how differences in implementation affected trade in relevant products. We find strong evidence that those EU member states that implemented the directive to a large extent had substantially higher import volumes at lower prices in environmental products. For certain environmental products, exports equally increased. Our paper is the first to show that the implementation of environmental regulation can spur international trade in environmental products.
Keywords: F14; 330; Climate change; Environment; Industry and trade